2017
DOI: 10.1007/s11748-017-0855-0
|View full text |Cite
|
Sign up to set email alerts
|

Is there a role for biomarkers in thoracic aortic aneurysm disease?

Abstract: Thoracic aortic aneurysm (TAA) represents a major cause of mortality and morbidity in Western countries. The natural history of TAA is indolent, with patients usually being asymptomatic until a catastrophic event such as rupture or dissection ensues. As such, early diagnosis is crucial and the search is ongoing for a biomarker that can indicate the presence of TAA with sufficient accuracy to act as a screening tool. To date, no such marker has been developed for the diagnosis of non-familial or 'sporadic' TAA.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 57 publications
0
21
0
Order By: Relevance
“…Imaging techniques such as computed tomography (CT), magnetic resonance imaging (MRI) and ultrasound are currently used for routine diagnosis and monitoring of aneurysms. However, these imaging tools cannot be used to accurately determine the pre-clinical status and predict the timing for dissection or rupture of aneurysms (reviewed in 53 ). It has been reported that aortic size does not always provide an accurate prediction for Type A or Type B aortic dissection 5456 .…”
Section: Discussionmentioning
confidence: 99%
“…Imaging techniques such as computed tomography (CT), magnetic resonance imaging (MRI) and ultrasound are currently used for routine diagnosis and monitoring of aneurysms. However, these imaging tools cannot be used to accurately determine the pre-clinical status and predict the timing for dissection or rupture of aneurysms (reviewed in 53 ). It has been reported that aortic size does not always provide an accurate prediction for Type A or Type B aortic dissection 5456 .…”
Section: Discussionmentioning
confidence: 99%
“…We expected a molecular, whose concentration positive correlation with pathology, is convenient to be detected before rupture even obvious dilatation occurs in aortic (Balmforth et al, ). Unfortunately, the ideal biomarker still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Syndromic causes are the chief associated or causative pathologies behind the genetics of TAAD: all identified syndromes have effects on vessel integrity and the associated TAAD sudden deaths commonly plague these patients. Marfan syndrome (MFS, OMIM 154700) is an autosomal dominant connective tissue disorder that typically affects the skeletal and cardiovascular system ( 12 , 13 ). While MFS is associated with Marfan locus on chromosome 15, presentation remains highly variable ( 14 , 15 ).…”
Section: Genetics Of Aortic Aneurysm and Dissectionmentioning
confidence: 99%